Development and validation of high-resolution melting markers derived from Ry sto STS markers for high-throughput marker-assisted selection of potato carrying Ry sto - Nie, X.; Sutherland, D.; Dickison, V.; Singh, M.; Murphy, A.M.; Koeyer, D. de (Scientific Societies, 2016)
Sequence analysis of the chromosome region harboring the sequence-tagged site (STS) markers YES3-3A and YES3-3B for Rysto, a gene responsible for extreme resistance to Potato virus Y (PVY) in potato, was performed in tetraploid potato ‘Barbara’ (Rrrr) and ‘AC Chaleur’ (rrrr) as well as their progeny selections. Three and two sequence variants were identified in Barbara resistant (R) selections and AC Chaleur susceptible (S) selections, respectively. Further analysis indicates that the variant with a 21-nucleotide (nt) deletion is likely the chromosome copy harboring the STS markers. Two primer pairs, one targeting the region containing a 20-nt deletion and the other targeting the region anchoring the YES3-3A reverse primer, were designed. As anticipated, pair one produced two visible fragments in Barbara-R bulk and one visible fragment in AC Chaleur-S bulk; pair two produced one visible fragment in all samples. When subjected to high-resolution melting (HRM) analysis, two distinct melting profiles for R and S samples were observed. Analysis of 147 progeny of Barbara × AC Chaleur revealed 72 and 75 progeny with R and S melting profiles, respectively, which was consistent with YES3-3A and YES3-3B assays and phenotyping analysis, thus demonstrating the potential of HRM profiles as novel molecular markers for Rysto. The efficacy of the newly developed HRM markers for high-throughput marker-assisted selection for Rysto-conferred resistance to PVY was validated further with three populations involving Barbara as the R parent.